2020
DOI: 10.3390/ijerph17082689
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Biomass Characteristics of SBRs Treating High-Salinity Wastewater at Presence of Anionic Surfactants

Abstract: Sodium dodecylbenzene sulfonate (SDBS) and sodium dodecyl sulfate (SDS), as two anionic surfactants, have diffused into environments such as surface water and ground water due to extensive and improper use. The effects on the removal performance and microbial community of sequencing batch reactors (SBRs) need to be investigated in the treatment of saline wastewater containing 20 g/L NaCl. The presence of SDS and SDBS could decrease the removal efficiencies of ammonia nitrogen and total phosphorus, and the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Concurrently, numerous scholars have conducted research on the application of surfactants. In the field of wastewater treatment, Li et al [14] found in 2020 that SDBS can affect the biological nitrogen and phosphorus removal efficiency in high-salinity wastewater treatment. YIN C et al [15] also found that surfactants can have a serious impact on denitrification-related bacteria in wastewater treatment in the same year.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, numerous scholars have conducted research on the application of surfactants. In the field of wastewater treatment, Li et al [14] found in 2020 that SDBS can affect the biological nitrogen and phosphorus removal efficiency in high-salinity wastewater treatment. YIN C et al [15] also found that surfactants can have a serious impact on denitrification-related bacteria in wastewater treatment in the same year.…”
Section: Introductionmentioning
confidence: 99%
“…Many treatment methods have been utilized at different stages of MWW treatment for discharge and reuse. These include, but not limited to, conventional filtration processes, coagulation-flocculation, sedimentation, and biological treatment methods [8]. Advanced 2 of 12 treatment methods include membrane processes and advanced oxidation processes.…”
Section: Introductionmentioning
confidence: 99%